A randomized study of multimedia informational aids for research on medical practices: Implications for informed consent. (February 2017) - Kraft, Stephanie A; Constantine, Melissa; Magnus, David; Porter, Kathryn M; Lee, Sandra Soo-Jin; Green, Michael; Kass, Nancy E; Wilfond, Benjamin S; Cho, Mildred K
Background/Aims: Participant understanding is a key element of informed consent for enrollment in research. However, participants often do not understand the nature, risks, benefits, or design of the studies in which they take part. Research on medical practices, which studies standard interventions rather than new treatments, has the potential to be especially confusing to participants because it is embedded within usual clinical care. Our objective in this randomized study was to compare the ability of a range of multimedia informational aids to improve participant understanding in the context of research on medical practices. Methods: We administered a web-based survey to members of a proprietary online panel sample selected to match national US demographics. Respondents were randomized to one of five arms: four content-equivalent informational aids (animated videos, slideshows with voice-over, comics, and text) and one no-intervention control. We measured knowledge of research on medical practices using a summary knowledge score from 10 questions based on the content of the informational aids. We used analysis of variance and paired t-tests to compare knowledge scores between arms. Results: There were 1500 completed surveys (300 in each arm). Mean knowledge scores were highest for the slideshows with voice-over (65.7%), followed by the animated videos (62.7%), comics (60.7%), text (57.2%), and control (50.3%). Differences between arms were statistically significant except between the slideshows with voice-over and animated videos and between the animated videos and comics. Informational aids that included an audio component (animated videos and slideshows with voice-over) had higher knowledge scores than those without an audio component (64.2% vs 59.0%, p < .0001). There was no difference between informational aids with a character-driven story component (animated videos and comics) and those without. Conclusion: Our results show that simple multimedia aids that use a dual-channel approach, such as voice-over with visual reinforcement, can improve participant knowledge more effectively than text alone. However, the relatively low knowledge scores suggest that targeted informational aids may be needed to teach some particularly challenging concepts. Nonetheless, our results demonstrate the potential to improve informed consent for research on medical practices using multimedia aids that include simplified language and visual metaphors.